(NiZGIB TRANSWERSALXNO(B-(NIZOTROPNYH PLASTIN S DEFEKTAMI TIPA TRE]IN (B/s - (NmAZURAK(B, (Nl@BOMIR pETROWI^s; (NbEREVNICKIJ(B, (NlEW tEODOROWI^s; (NrOMANIW(B, (No(B. (Nn(B.s ((NkIEW (B:s (NnAUKOWA DUMKA(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 242-251 (232 (NNAZW(B.)s
(Nan ussr(B, (NfIZ(B.-(NMEH(B. (NIN(B-(NTs
Keywords: (NwLIQNIE TRE]INs; (NiZGIBs; (NnAPRQVENIQs; (NpLASTINYs; (NpLASTINY IZOTROPNYEs